Brazilian gold in the eighteenth century: a reassessment - Costa, Leonor Freire (2010)
This working paper aims to provide data gathered in a research program developed by Gabinete de História Económica e Social (GHE.S) on gold remittances from Brazil in the 18th century. Results of this project revise published accounts of bullion flows in the 18th century with regard to the Brazilian contribution to the European money stock. This is a preliminary presentation of results that support the thesis and arguments in a forthcoming book entitled O ouro do Brasil no século XVIII: remessas e agentes.